Evaluación técnica financiera del uso de la herramienta "Sand Jetting" con unidad de coiled tubing en procesos de abandono definitivo (2020)
For this purpose, the national normative guidelines for abandonment of wells and the Norsok D-010 guideline were considered as the basis for the needed techniques and operations to design the new abandonment methodology. This methodology was implemented in the Circle 7 well, being the prospective well due to the absence of cement in the cladding annulus of the 9-5/8'' and 7 '' due to the fact that economically in Colombia the production casing is not cemented to surface, the current document highlights, evaluates and argues the abandonment technique with Sand jetting and coiled tubing with a total cost of USD 104,624 lower than the average cost associated with the definitive abandonment of previous company wells for a value of USD 262,977 on average. determined the viability in the project was reflected with cement returns, positive pressure and bubble tests thus achieving the final abandonment of the Circle 7 well.